Airborne Stability of Simian Virus 40 - Akers, T. G. (1973)
The influence of relative humidity on the airborne survival of simian virus 40 (SV40) was studied by allowing virus aerosols to age in rotating drums at 21 or 32 C and at a relative humidity (RH) value ranging from 22 to 88%. Airborne SV40 virus was stable at every RH tested at 21 C, but aerosols maintained at 32 C were inactivated within 60 min at mid-range RH values. The unusual stability at 21 C over a broad RH range indicates that potentially biohazardous situations may occur under laboratory conditions if this virus becomes accidentally airborne.